Assess the status of small and medium enterprises in Kaisonephomvihan and Othoumphone district Savannakhet Province - SYHACHACK, Mithsy; MANIVONG, Khamkeo; SACBOUAVONG, Khoune (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The study was to study the development of small your own medium to enhance the ability to conduct business is important and much needed now by the operators present in the province of Savannakhet in particular in the municipality are very reasonable with the purpose of the study (1) to study the problems of operators of small and medium, (2) to study the strategy and the development of business entrepreneurs and businesses small and medium The sample used in the study was 341 units, the data collection tools were not questionnaires, the data were analyzed by SPSS program and the basic statistical values average, percentage and standard deviation. Findings: (1) from the analysis of data on the problems of small and medium-sized enterprises, the labor problems are at a high level, with the average and standard deviation equal to (= 3.90; S.D = 0.83) most of the labor problem is in the family is not at a higher level because most businesses have personnel in the family, so it is difficult to manage, the problem of lack of capital is at a high level with an average value and standard deviation equal to (= 3.88); S.D = 0.30; Most of the labor problem is in the family is not at a higher level because most businesses have personnel in the family, so it is difficult to manage, the problem of lack of capital is at a high level with an average value and standard deviation equal to (= 3.88); S.D = 0.30) among them, the problem of financial institutions providing capital on demand and promptness is not at a higher level because the process of borrowing is still complex and there are many steps, the problem of marketing problems, the problem of lack of capital is at a high level with average and standard deviations equal to (= 3.86; S.D=0.30), business problems are at a high level with average and standard deviations equal to (= 3.85; S.D = 0.46) and management problems are at a high level with average and standard deviations equal to (= 3.69; S.D = 0.31). The adjustment of the system to keep pace with changes in environmental factors is not at a high level because the economic situation and the fast-changing exchange rate is a problem in the management. (2) from the analysis of data on strategies and guidelines for the development of small and medium-sized businesses, the product strategy is at a high level, with the average value and standard deviation equal to (= 4.05; S.D = 0.42), The management strategy is at a higher level because: business units have a need to distribute products to consumers, and business development pathways are at a higher level, with an average value and standard deviation equal to (= 3.49; S.D = 0.76). Reducing taxes on the growth of small and medium-sized businesses and joint ventures is at a much higher level because lowering taxes will enable businesses to grow and reduce costs. Provide import and export tax reductions to create conditions for small and medium enterprises to grow in order to have liquidity in doing business, encourage entrepreneurs to focus on personnel development, especially in the field of marketing or promotion in the field of marketing. to strengthen the mechanism and network for the promotion of small and medium-sized businesses, to develop the database system for small and medium-sized businesses to be up-to-date, to facilitate investment The multi-step documentation process takes several days, providing training for entrepreneurs, especially to enhance knowledge, skills, experience, such as business planning, production cost calculation and profit margin calculation.